Being the Shī’te among the Sunni Majority in Indonesia: A Preliminary Study of Ustadz Husein Al-Habsyi (1921-1994) - Zulkifli, Zulkifli (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2004)
One of the important research topics related to the Arab communities in Indonesia, and in Southeast Asia in general, that is likely to be neglected is their adherence to the Shi'ah, a minority school of Islam that differs from the Sunni majority in terms of several principal doctrines. As far as Islamic studies and social scientists studying Islam are concerned, the Shi'ah outside Iran seems to be a neglected research topic. Studies of Islam in Indonesia, like those in the Middle East, are mainly studies of the Sunni school. Therefore, aspects of the social, political, economic, and religious life of the Shi'ites in Indonesia remain unknown to scholars of Indonesian Islam as well as to Indonesianists.DOI: 10.15408/sdi.v11i2.603